2016
DOI: 10.1371/journal.pone.0167052
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497 Induces Apoptosis and Suppresses Proliferation via the Bcl-2/Bax-Caspase9-Caspase3 Pathway and Cyclin D2 Protein in HUVECs

Abstract: IntroductionMicroRNAs play crucial roles in various types of diseases. However, to date, no information about the role of miR-497 in the development of atherosclerosis has been reported. This study investigated the possible role of miR-497 in vascular endothelial cell injury during the early stage of atherosclerosis.Materials and MethodsThe expression level of miR-497 in human umbilical vein endothelial cells (HUVECs) exposed to ox-LDL was detected using qRT-PCR. To perform gain of function and loss of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 42 publications
7
55
0
Order By: Relevance
“…Furthermore, certain Bcl-2 family proteins have previously been found to be modulated in apoptosis progression. The balance between pro-and anti-apoptotic members of the Bcl-2 family proteins decides the fate of the cell, and an increased proportion of pro-apoptotic proteins results in apoptotic cell death (45,46). In the present study, β-elemene with hyperthermia induced apoptosis in A549 cells, and also increased Bax expression and decreased Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, certain Bcl-2 family proteins have previously been found to be modulated in apoptosis progression. The balance between pro-and anti-apoptotic members of the Bcl-2 family proteins decides the fate of the cell, and an increased proportion of pro-apoptotic proteins results in apoptotic cell death (45,46). In the present study, β-elemene with hyperthermia induced apoptosis in A549 cells, and also increased Bax expression and decreased Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 52%
“…One of the pivotal apoptosis regulation mechanisms is the cellular intrinsic mitochondrial pathway (Parrish et al, 2013), which could be escaped in tumor cells by modulating anti-apoptotic or pro-apoptotic molecules (Igney and Krammer, 2002). The Caspase and Bcl-2 protein families are essential apoptosis-related proteins, which can initiate mitochondrial-dependent apoptosis pathway (Martinou and Youle, 2011;Gui et al, 2012;Wu et al, 2016). A large number of studies have shown that aberrant activation of these proteins could result in excessive proliferation of most malignant tumor cells, including CML (Reed, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important executioners in the apoptotic process, caspase‐3 contains a cysteine residue (Cys‐163) and a histidine residue (His‐121) that act to stabilize the peptide bond cleavage of the target protein sequence to the carboxy‐terminal side of an aspartic acid when it is part of a particular 4‐amino acid sequence (Asp‐x‐x‐Asp) . Caspase‐3 has been identified as the downstream of p53, TLR4‐ERK1/2‐Fas/FasL, Bcl‐2/Bax‐Caspase9 and JNK/c‐Jun, and plays vital roles in the genesis and development of multiple type of cancers. In our study, we demonstrated that HOXC13 represses transcription of CASP3 by directly targeting its promotor region, thereby exhibiting its oncogenic role in ESCC.…”
Section: Discussionmentioning
confidence: 99%